2011
DOI: 10.1007/s11738-011-0918-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of oat cultivars to phosphate deprivation: plant growth and acid phosphatase activities

Abstract: The effect of phosphate starvation on growth and acid phosphatases (APases) localization and activity in oat tissues was investigated. Oat cultivars (Avena sativa L.-Arab, Polar, Szakal) were grown for 1-3 weeks in complete nutrient medium (?P) and without phosphate (-P). Pi concentration in plant tissues decreased strongly after culturing on -P medium. Pi deficit reduced shoot growth, stimulated root elongation and increased ratio of root/shoot in all oat cultivars. Pi deficit had a greater impact on growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 39 publications
4
25
0
1
Order By: Relevance
“…To determine nodule surface acid phosphatase activity, whole nodules (approximately 3 g fresh weight [fw]) were washed in distilled water, blotted dry and placed into 5ml of incubation medium with substrate mixture (6 mM para-nitrophenylphosphate (pNPP) and 1 mM dithiothreitol (DTT) in 50 mM Na-acetate buffer, pH 5.0), and incubated at 25 °C (Zebrowska et al 2012, Ciereszko et al 2002. After 30 min, 100 µl of the reaction medium was removed and added to 100 µl 1M of NaOH to stop the reaction.…”
Section: Extracellular Acid Phosphatase Assaymentioning
confidence: 99%
“…To determine nodule surface acid phosphatase activity, whole nodules (approximately 3 g fresh weight [fw]) were washed in distilled water, blotted dry and placed into 5ml of incubation medium with substrate mixture (6 mM para-nitrophenylphosphate (pNPP) and 1 mM dithiothreitol (DTT) in 50 mM Na-acetate buffer, pH 5.0), and incubated at 25 °C (Zebrowska et al 2012, Ciereszko et al 2002. After 30 min, 100 µl of the reaction medium was removed and added to 100 µl 1M of NaOH to stop the reaction.…”
Section: Extracellular Acid Phosphatase Assaymentioning
confidence: 99%
“…Oat is usually cultured on poor soils, with a low mineral concentration, but its acclimation mechanisms to such environment are not fully understood. Our previous results indicated that oat cultivars differed in terms of acclimation to Pi starvation [38]. In the present study, the effects of differential phosphorus supply (inorganic and organic P or no P) on oat growth and acid phosphatase activity and localization were investigated to estimate the role of these enzymes in oat response to Pi deficiency.…”
Section: Introductionmentioning
confidence: 93%
“…Oat seedlings (Avena sativa L. ' Arab'), after 7 days of germination (on Petri dishes), were grown hydroponically on nutrient media with contrasting P sources: inorganic phosphate, KH 2 PO 4 (+P, control), lowered Pi concentration to 0.1 of the control (0.1 P), phytic acid (PA) as organic source of P, or without phosphate (−P) in conditions similar to that used by Ciereszko et al [10] and Żebrowska et al [38]. The control nutrient medium contained: Ca(NO 3 …”
Section: Plant Materials and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Figura 14 -Determinação da atividade da fosfatase ácida em folhas recém-expandidas em plantas de pinhão-manso desenvolvidas em solução completa e com a omissão de P, aos 20, 30, 40 e 120 dias após o início dos tratamentos A alta atividade da enzima fosfatase ácida como resposta adaptativa à baixa disponibilidade de fósforo tem sido observada em diversas culturas (NUNES et al, 2008;GAUME et al, 2010;ZEBROWSKA;BUJNOWSKA;CIERESZKO, 2011). Em condições de baixa disponibilidade de fósforo, as plantas utilizam a fosfatase ácida para promover a desfosforilação de compostos orgânicos disponibilizando fósforo inorgânico para manutenção do metabolismo celular em regiões meristemáticas (TOMSCHA et al, 2004;TRAN;HURLEY;PLAXTON,2010).…”
Section: Atividade Da Fosfatase áCidaunclassified